Expanding the realm of possibilities: the role of informal STEM programs in promoting STEM major and STEM career awareness - Habig, Bobby; Geller, Franny; Gupta, Preeti; Adams, Jennifer D.; Holford, Mandë (Frontiers in Education, 2026)
A significant challenge is to identify strategies that motivate youth to consider a STEM career pathway. For many young people, the first barrier to entry is lack of awareness of STEM majors and careers. Promisingly, informal STEM programs are potential vehicles for addressing issues of underrepresentation and for bolstering youths’ knowledge and understanding of STEM career pathways. The goal of this study was to conduct a meta-synthesis of research on the outcomes of participants of informal STEM programs. We used a mixed methods approach to address three research questions: (1) How and to what extent do informal STEM learning experiences impact K-12 participants’ knowledge and understanding of STEM career pathways and careers? (2) What are program design principles, effective practices, and technological innovations of rigorously designed studies that exhibit strong or exemplary evidence of impact? (3) What strategies work most effectively in underserved populations? Across the informal STEM education landscape, we found that many studies exhibited weak or adequate research design. However, among rigorously designed studies, we found a significant positive association between participation in informal STEM programs and increased STEM career awareness (Cohen’s d = 0.584, 95% CI: 0.295–0.872, p < 0.001). Our meta-syntheses revealed that informal STEM programs that target high school students, girls, or members of historically underrepresented groups, and that focus on career exploration and experiential learning were most effective at fostering STEM career awareness. Our results suggest that informal STEM institutions play an unappreciated role in ensuring that youth are introduced to potential future careers. Critically, our findings can be used by practitioners to inform program design and confront issues of underrepresentation.